Physiological Measurements and Transcriptome Survey Reveal How Semi-mangrove Clerodendrum inerme Tolerates Saline Adversity - Liang, Minting; Hu, Feng; Xie, Dongsheng; Chen, Zhibin; Zheng, Qingzhi; Xie, Qiyun; Zheng, Feng; Liu, Dongming; Jian, Shuguang; Chen, Hongfeng; Liu, Xuncheng; Wang, Faguo (Frontiers in Plant Science, 2022)
Salinity adversity has been a major environmental stressor for plant growth, development and reproduction worldwide. Halophyte Clerodendrum inerme, a naturally salt-tolerant plant, can be studied as a success example to understand biological mechanism to saline resistance. As plants respond in many ways to salinity and at a number of levels, our greenhouse study interpreted the response of C. inerme to salt stress by means of morphology, osmotic protectants, ROS production and scavenging, ion homeostasis, photosynthetic efficiency, and transcriptome reprofiling to illustrate its tolerant process from salt acclimatization (till medium NaCl level, 0.3 mol/L) to salinity stress (high NaCl level, 0.5 mol/L). The overall evaluation of performance leads to a conclusion that the main survival strategy of C. inerme collectively regulating the salinity stress response seems metabolic and ion global reshaping. These findings uncover mechanistic framework by which C. inerme modifies its development to resist the short- and long-term salt adversity, as well as rebalance the energy allocation between growth and stress tolerance.